Utilization method of auxiliary product resin in decommissioned carbon fiber reinforced resin-based composite material and prepared anticorrosive coating
By using cerium oxide and molten salt in molten salt to recover carbon fibers, separate and compound resin components, the problems of poor product complexity and homogeneity in thermosetting resin recycling are solved, and the efficient dissociation of the resin and the improvement of economic value are achieved. , promotes the recycling of carbon fiber composite materials.
Patent Information
- Application Number
- CN202411325544.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The products produced by thermosetting resins during the recycling process are complex in composition, poor homogeneity, low economic value, and difficult to achieve high-value utilization.
Carbon fiber is recovered using cerium oxide and molten salt in the molten salt pool, the phenol-rich phase is separated, and combined with epoxy chloride and epoxy resin to prepare an anticorrosion coating to enhance the homogeneity and economic value of the resin decomposition products.
It realizes efficient dissociation of resin, improves the orientation of key components of resin decomposition products, improves the economic value of the attached product resin, and promotes the whole material recycling and recycling of carbon fiber composite materials.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of resin material recycling, and specifically relates to a method for utilizing by-product resin in retired carbon fiber reinforced resin-based composite materials and an anti-corrosion coating prepared therefrom. Background Art
[0002] In recent years, carbon fiber, with its excellent low-density, high-strength properties, has been extensively used in aerospace, wind power generation, and hydrogen storage vessels. As the application of carbon fiber continues to surge, the need for its recycling has become increasingly prominent. In the carbon fiber matrix market, thermosetting resins dominate due to their excellent mechanical properties and synthetic advantages. Their cross-linking properties enable the resulting carbon fiber composites to possess superior overall performance. However, the stable three-dimensional network structure generated by cross-linking makes it more difficult to break down during the recycling process, making the targeted recycling of carbon fiber a challenge.
[0003] To address this challenge, existing recycling technologies often employ more drastic methods to break down the three-dimensional network structure. For example, pyrolysis, the only technology currently capable of commercial application, produces products with complex composition, poor homogeneity, and low economic value, making it difficult to develop high-value utilization pathways.
[0004] Patent publication number CN 108779284 A, "Method for Recovering Decomposition Products of Cured Thermosetting Resin and Method for Producing Recycled Materials," published on November 9, 2018, discloses the following steps: contacting a treatment object containing a cured thermosetting resin with a treatment solution containing an alkali metal compound and an alcohol solvent to decompose and dissolve the cured thermosetting resin; mixing the treatment solution containing the decomposition products of the cured thermosetting resin with an acidic aqueous solution and separating the mixture into an aqueous layer and an organic layer containing the decomposition products; and recovering the organic layer. However, the patent does not disclose how to homogenize the resin decomposition products.
[0005] If efficient dissociation of resin in composite materials can be achieved and the key components of resin decomposition products can be targetedly improved, the economic value of the by-product resin will be further enhanced, and the full material recycling of carbon fiber composite materials will be promoted. Summary of the Invention
[0006] The purpose of the present invention is to provide a method for utilizing the by-product resin in retired carbon fiber reinforced resin-based composite materials and an anti-corrosion coating prepared therefrom, a method for recovering carbon fibers using cerium oxide and molten salt, obtaining a phenol-rich phase, adding epichlorohydrin for conditioning, compounding with epoxy resin, and curing to obtain an anti-corrosion coating that can be used for metal corrosion protection. The present invention can effectively solve the problems of complex composition, poor homogeneity, and low economic value of products generated after thermal cracking of thermosetting resins. The method for utilizing the by-product resin in retired carbon fiber reinforced resin-based composite materials provided by the present invention can achieve efficient dissociation of the resin and directional improvement of key components of the resin decomposition products.
[0007] The specific technical solutions of the present invention are as follows:
[0008] A method for utilizing by-product resin in retired carbon fiber reinforced resin-based composite materials, specifically comprising:
[0009] 1) In a molten salt pool, the retired carbon fiber reinforced resin-based composite material is mixed with molten salt containing CeO2, heated and kept warm, the carbon fiber is separated, and the liquid phase product is collected;
[0010] 2) distilling the liquid product to separate the aqueous phase and the phenol-rich phase;
[0011] 3) adding epichlorohydrin to the phenol-rich phase for conditioning;
[0012] 4) adding epoxy resin and solvent to the tempered phenol-rich phase to obtain a metal anti-corrosion paint.
[0013] In step 1), the mass ratio of the retired carbon fiber reinforced resin-based composite material to the molten salt containing CeO2 is greater than 10:1.
[0014] In step 1), the carbon fiber reinforced resin-based composite material refers to a carbon fiber and epoxy resin-based composite material; preferably, the carbon fiber reinforced resin-based composite material is selected from the carbon fiber reinforced resin-based composite material used in hydrogen storage containers or wind turbine blades.
[0015] In step 1), the molten salt contains CeO2, and the mass ratio of CeO2 in the molten salt is 5-10%, preferably 8%;
[0016] In step 1), the molten salt is selected from one or more of chloride salts, alkali salts or carbonates. Preferably, the molten salt is selected from ZnCl2-KCl molten salt or Li2CO3-Na2CO3-K2CO3 molten salt;
[0017] In step 1), the heating and heat preservation temperature is 400-800° C. and the time is 0.5-1 h;
[0018] In step 1), the separation of carbon fibers is specifically as follows: a winding device is set in the molten salt pool, which can rotate clockwise at a low speed to wind the carbon fibers onto the winding device, and then the winding device leaves the molten salt pool, enters the water pool, and then rotates counterclockwise to remove the fibers, thereby completing the recovery of the carbon fibers after the molten salt electrolysis reaction.
[0019] In step 1), the liquid phase product is obtained by condensation separation.
[0020] In step 2), the liquid product is distilled to separate a water phase and a phenol-rich phase; the water phase has a boiling point of 100° C., the obtained water phase is discarded, and the phenol-rich phase has a boiling point of 200-300° C. and is collected for subsequent use.
[0021] In step 3), epichlorohydrin is added to the phenol-rich phase in a mass ratio of 1:6 to 1:10. The phenol-rich phase comprises components such as p-isopropylphenol, bisphenol A, and bisphenol F. The purpose of step 3) is to allow the phenol-rich phase to undergo a polymerization reaction to produce a bisphenol A epoxy resin.
[0022] Step 3) specifically comprises: mixing epichlorohydrin and the phenol-rich phase, then heating in a water bath to 70-80°C, adding a 25-30 wt% sodium hydroxide solution in a ratio of 1:1 between the total volume of epichlorohydrin and the phenol-rich phase and the sodium hydroxide solution, and maintaining the mixture in the water bath for 2 hours. Equal volumes of benzene and distilled water are added, the mixture is stirred, and the mixture is allowed to stand for separation. The resulting oil is distilled to remove water, benzene, and excess epichlorohydrin, thereby obtaining the tempered phenol-rich phase.
[0023] In step 4), the mass ratio of the phenol-rich phase, epoxy resin and solvent after conditioning is 1:10:1.
[0024] In step 4), the epoxy resin is selected from E-44 or E-51.
[0025] In step 4), the solvent is selected from a strong polar solvent, preferably acetone.
[0026] This invention uses a CeO2 catalyst dispersed at a mass ratio of 5-10% in a molten salt system. The molten salt catalyzes the cracking of a resin matrix to produce a phenol-rich fraction, which is then fractionated according to boiling point. This fraction is then used as a raw material for re-preparing resin. The method also develops a method for preparing metal coatings and re-combining it with fibers to create composite materials. The distilled phenol-rich phase is then mixed with epichlorohydrin and then epoxy resin to produce an anti-corrosion paint, enabling the recycling of retired materials.
[0027] The present invention provides an anti-corrosion coating, which is a metal anti-corrosion paint obtained by the method of utilizing the by-product resin in the retired carbon fiber reinforced resin-based composite material, and is coated on the metal surface and cured to obtain the anti-corrosion coating.
[0028] The curing step is to raise the temperature to 150-180° C. at a rate of 3-5° C. / min and keep the temperature for 0.5-1 hour.
[0029] The thickness of the anti-corrosion coating is 3-5 mm.
[0030] The metal anticorrosion paint prepared by the method of utilizing the byproduct resin in the retired carbon fiber reinforced resin-based composite material provided by the present invention has an anticorrosion coating obtained after curing, which has good anticorrosion effect and stable coating properties.
[0031] When the fiber is taken out, a turntable is set in the molten salt pool, which can rotate clockwise at a low speed to wind the fiber on the turntable. Then the turntable leaves the molten salt pool, enters the water pool and rotates counterclockwise to turn the fiber down to complete the molten salt reaction and recover the fiber.
[0032] Compared with the prior art, in the present invention, the addition of a Ce-based catalyst to the molten salt system can effectively increase the reaction rate, reduce the yield of coke, increase the yield of liquid phase products, and have good anti-coking properties. It has a strong selectivity for the cracking of the resin matrix, can reduce the energy barrier, and selectively break the CO ether single bond, so that the resin matrix can be depolymerized to generate more short molecular chain compounds. It also has a very high oxygen exchange capacity and storage capacity, can effectively reduce the amount of free oxygen, and promote the formation of hydroxyl radicals by thermal activation, thereby increasing the content of oxygen-containing components in the liquid phase product. Cerium oxide particles have a high dispersion rate and suspension stability in thick liquids, so molten salt and cerium oxide particles can be combined to form a more stable and efficient dispersion system, thereby improving the efficiency of resin catalytic cracking. DETAILED DESCRIPTION
[0033] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0034] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0035] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions.
[0036] Example 1
[0037] A method for utilizing by-product resin in retired carbon fiber reinforced resin-based composite materials, specifically comprising:
[0038] 1) In a molten salt pool, a ZnCl2-KCl molten salt containing 8wt% CeO2 was first heated to a preset temperature of 600°C and held at that temperature for 1 hour. Decommissioned carbon fiber-reinforced epoxy resin composite materials were then added and held at 600°C for 0.5 hours, resulting in a liquid product yield of 63%. The mass ratio of the decommissioned carbon fiber-reinforced epoxy resin composite materials to the CeO2-containing molten salt was 12:1. The carbon fiber-reinforced epoxy resin composite materials used are wind turbine blade materials. For example, for a 50-meter-long wind turbine blade, the carbon fiber composite material accounts for approximately 20% of the main beam, with a carbon fiber to resin ratio of approximately 7:3. A winding device was also installed in the molten salt pool, capable of rotating clockwise at a low speed to wind the carbon fiber onto the winding device. The winding device then exited the molten salt pool, entered a water pool, and then rotated counterclockwise to remove the fiber, completing the recovery of the carbon fiber after the molten salt electrolysis reaction.
[0039] 2) distilling the liquid product obtained in step 1) and condensing to separate an aqueous phase and a phenol-rich phase; the aqueous phase is discarded, and the phenol-rich phase accounts for 71% of the liquid product;
[0040] 3) Add epichlorohydrin to the phenol-rich phase in a mass ratio of 1:6. Heat the mixture in a water bath to 80°C. Add 30 wt% sodium hydroxide solution in a ratio of 1:1 (total volume of epichlorohydrin: phenol-rich phase: sodium hydroxide solution). Maintain the mixture in the water bath for 2 hours. Add equal volumes of benzene and distilled water, stir, and allow the mixture to stand for separation. Distill the resulting oil to remove water, benzene, and excess epichlorohydrin, thereby obtaining the conditioned phenol-rich phase.
[0041] 4) adding epoxy resin E-44 and solvent acetone to the conditioned phenol-rich phase, wherein the mass ratio of the conditioned phenol-rich phase, epoxy resin, and solvent is 1:10:1, and mixing well to obtain a metal anticorrosion paint.
[0042] The metal anticorrosive paint prepared in Example 1 was applied to the metal surface, and the temperature was raised to 150° C. at a rate of 3-5° C. / min and kept at that temperature for 1 hour for curing to obtain an anticorrosive coating having a thickness of 4 mm.
[0043] Comparative Example 1
[0044] A method for utilizing by-product resin in retired carbon fiber reinforced resin-based composite materials, specifically comprising:
[0045] 1) In a molten salt pool, a ZnCl2-KCl molten salt was first heated to a preset temperature of 600°C and held at that temperature for 1 hour. Decommissioned carbon fiber-reinforced epoxy resin-based composite materials were then added and held at 600°C for 0.5 hour, yielding a 37% liquid product yield. The mass ratio of the decommissioned carbon fiber-reinforced resin-based composite materials to the molten salt was 12:1, and the carbon fiber-reinforced resin-based composite materials used were the same as those in Example 1. A winding device was also provided in the molten salt pool, capable of rotating clockwise at a low speed to wind the carbon fibers around the winding device. The winding device then left the molten salt pool, entered a water pool, and then rotated counterclockwise to remove the fibers, completing the recovery of the carbon fibers after the molten salt electrolysis reaction.
[0046] 2) distilling the liquid product and condensing to separate a water phase and a phenol-rich phase; the water phase is discarded, and the phenol-rich phase content in the liquid product accounts for 31%;
[0047] 3) adding epichlorohydrin to the phenol-rich phase, and the conditioning reaction process is the same as in Example 1;
[0048] 4) Adding epoxy resin and solvent to the tempered phenol-rich phase, using the same raw materials and methods as in Example 1, to obtain a metal anticorrosive paint.
[0049] According to the same method and parameters as in Example 1, the metal anti-corrosion paint prepared in Comparative Example 1 was applied to the metal surface and cured to obtain an anti-corrosion coating.
[0050] Comparison of Example 1 and Comparative Example 1 shows that the molten salt system in Example 1 contains CeO2, the liquid phase product yield is high, and the proportion of phenol-rich components after distillation is high. The reaction only takes 0.5h, indicating that the CeO2-containing catalyst of the present invention can effectively increase the reaction rate and increase the yield of the liquid phase product. It has a strong selectivity for the cracking of the resin matrix, can reduce the energy barrier, and selectively break the CO ether single bond, so that the resin matrix can be depolymerized to generate more short molecular chain compounds (phenol-rich phase), which is beneficial to the recycling of digital materials.
[0051] Example 2
[0052] A method for utilizing by-product resin in retired carbon fiber reinforced resin-based composite materials, specifically comprising:
[0053] 1) In a molten salt pool, a Li2CO3-Na2CO3-K2CO3 molten salt containing 8wt% CeO2 was first heated to a preset temperature of 700°C and held for 1 hour. A retired carbon fiber-reinforced epoxy resin-based composite material was then added and held for 0.5 hour, yielding a liquid product with a yield of 84%. The mass ratio of the retired carbon fiber-reinforced resin-based composite material to the Li2CO3-Na2CO3-K2CO3 molten salt containing 8wt% CeO2 was 15:1, and the carbon fiber-reinforced resin-based composite material used was a wind turbine blade material, as in Example 1. A winding device was also provided in the molten salt pool, capable of rotating clockwise at a low speed to wind the carbon fiber around the winding device. The winding device then left the molten salt pool, entered a water pool, and then rotated counterclockwise to remove the fiber, completing the recovery of the carbon fiber after the molten salt electrolysis reaction.
[0054] 2) distilling the liquid product and condensing to separate the aqueous phase and the phenol-rich phase; the aqueous phase is discarded, and the phenol-rich phase accounts for 83% of the liquid product;
[0055] 3) Add epichlorohydrin to the phenol-rich phase in a mass ratio of 1:10. Heat the mixture in a water bath to 70°C. Add a 25 wt% sodium hydroxide solution in a ratio of 1:1 (total volume of epichlorohydrin: phenol-rich phase: sodium hydroxide solution). Maintain the mixture in the water bath for 2 hours. Add equal volumes of benzene and distilled water, stir, and allow the mixture to stand for separation. Distill the resulting oil to remove water, benzene, and excess epichlorohydrin, thereby obtaining the conditioned phenol-rich phase.
[0056] 4) Adding E-51 epoxy resin and solvent acetone to the phenol-rich phase after conditioning, wherein the mass ratio of E-51 epoxy resin and solvent acetone to the phenol-rich phase after conditioning is 1:10:1, stirring and mixing to obtain a metal anti-corrosion paint.
[0057] The metal anti-corrosion paint prepared in Example 2 was applied to the metal surface, and the temperature was raised to 180° C. at a rate of 5° C. / min and kept warm for 0.5 h to obtain an anti-corrosion coating.
[0058] Comparative Example 2
[0059] A method for utilizing by-product resin in retired carbon fiber reinforced resin-based composite materials, specifically comprising:
[0060] 1) In a molten salt pool, the Li2CO3-Na2CO3-K2CO3 molten salt was first heated to a preset temperature of 700°C and held at that temperature for 1 hour. Decommissioned carbon fiber-reinforced epoxy resin-based composite materials were then added and held at that temperature for 0.5 hour, resulting in a liquid product yield of 52%. The mass ratio of the decommissioned carbon fiber-reinforced resin-based composite materials to the molten salt was 15:1, and the carbon fiber-reinforced resin-based composite materials used were the same as those in Example 2. A winding device was also installed in the molten salt pool, capable of rotating clockwise at a low speed to wind the carbon fibers around the winding device. The winding device then left the molten salt pool, entered a water pool, and then rotated counterclockwise to remove the fibers, completing the recovery of the carbon fibers after the molten salt electrolysis reaction.
[0061] 2) distilling the liquid product and condensing to separate a water phase and a phenol-rich phase; the water phase is discarded, and the phenol-rich phase accounts for 44% of the liquid product;
[0062] 3) Add epichlorohydrin to the phenol-rich phase and condition it. The specific process is the same as in Example 2.
[0063] 4) Adding epoxy resin and solvent to the tempered phenol-rich phase, and using the same raw materials and method as in Example 2, a metal anticorrosive paint was obtained.
[0064] According to the same parameters and methods as in Example 2, the metal anti-corrosion paint prepared in Comparative Example 2 was applied to the metal surface and cured to obtain an anti-corrosion coating.
[0065] Comparison of Example 2 and Comparative Example 2 shows that the molten salt in Example 2 contains 8% CeO2, the liquid phase product yield is high, and the proportion of phenol-rich components after distillation is high. The reaction only takes 0.5h, indicating that the CeO2-containing catalyst of the present invention can effectively increase the reaction rate and increase the yield of the liquid phase product. It has a strong selectivity for the cracking of the resin matrix, can reduce the energy barrier, and selectively break the CO ether single bond, so that the resin matrix can be depolymerized to generate more short molecular chain compounds (phenol-rich phase), which is beneficial to the recycling of digital materials.
[0066] The above embodiments are described to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for utilizing the byproduct resin in retired carbon fiber reinforced resin-based composite materials, It is characterized in that The utilization method comprises the following steps: 1) In a molten salt pool, the retired carbon fiber reinforced resin matrix composite material is mixed with CeO 2 Mixing with molten salt, heating and heat preservation, separating carbon fibers, and collecting liquid products; 2) distilling the liquid product to separate a water phase and a phenol-rich phase; 3) adding epichlorohydrin to the phenol-rich phase for conditioning; 4) Adding epoxy resin and solvent to the tempered phenol-rich phase to obtain a metal anticorrosive paint.
2. The method of utilizing according to claim 1, It is characterized in that In step 1), the retired carbon fiber reinforced resin matrix composite material is mixed with CeO 2 The mass ratio of molten salt is greater than 10:
1.
3. The method of using according to claim 1 or 2, It is characterized in that In step 1), the CeO 2 Molten salt, CeO 2 The mass ratio in molten salt is 5-10%.
4. The method of using according to claim 1 or 2, It is characterized in that In step 1), the molten salt is selected from one or more of chloride salts, alkali salts or carbonate salts.
5. The method of utilization according to claim 1 or 2, It is characterized in that In step 1), the heating and heat preservation has a temperature of 400-800° C. and a time of 0.5-1 h.
6. The method of utilizing according to claim 1, It is characterized in that In step 3), epichlorohydrin is added to the phenol-rich phase, and the mass ratio of the phenol-rich phase to epichlorohydrin is 1:6-1:
10.
7. The method of utilization according to claim 1 or 6, It is characterized in that Step 3) is specifically as follows: epichlorohydrin and the phenol-rich phase are mixed, and then heated in a water bath to 70-80° C., a sodium hydroxide solution with a mass concentration of 25-30wt% is added according to the total volume of epichlorohydrin and the phenol-rich phase: sodium hydroxide solution = 1:1, the water bath is maintained for 2 hours, an equal volume of benzene and distilled water are added, the mixture is stirred and mixed, and then the mixture is allowed to stand for stratification; the oily substance obtained by stratification is distilled to remove water, benzene and excess epichlorohydrin, so as to obtain a phenol-rich phase after conditioning.
8. The method of utilizing according to claim 1, It is characterized in that In step 4), the mass ratio of the phenol-rich phase, epoxy resin and solvent after conditioning is 1:10:
1.
9. The method of utilization according to claim 1 or 8, It is characterized in that In step 4), the epoxy resin is selected from E-44 or E-51; and the solvent is selected from acetone.
10. An anti-corrosion coating, It is characterized in that The metal anticorrosion paint obtained by the method for utilizing the byproduct resin in the retired carbon fiber reinforced resin-based composite material according to any one of claims 1 to 9 is applied on the metal surface and cured to obtain an anticorrosion coating.
Citation Information
Patent Citations
Method for recovering decomposition product of thermosetting resin cured product and method for producing regenerated material
CN108779284A
Catalyst and treatment method for upgrading tar by using catalyst
CN103447060A
Method for microwave pyrolysis of carbon fiber composite material
CN111100322A
High-solid-content epoxy zinc-rich anticorrosive paint and preparation method thereof
CN115851078A
Method for decomposing plastic-containing material, method for recovering inorganic material, regenerated carbon fiber and method for producing regenerated carbon fiber, blended yarn, carbon fiber-reinforced thermoplastic resin pellet containing said blended yarn and method for producing same, carbon fiber-reinforced thermoplastic resin strand and method for producing same, and carbon fiber-reinforced thermoplastic pellet
CN116034130A
Cited By
Fused salt pyrolysis recovery system and method for phenolic resin composite material
CN119839013A
